Electronic Criminal Trial Reform That Guarantees Due Process Of Law - Fendy Aditiya Siswa YULIANTO; Bambang SUGIRI (International Journal of Environmental, Sustainability, and Social Science, 2022)
This study examines how the reformulation of electronic criminal trials in Indonesia ensures the correct legal process. The research approach used is normative juridical law research, namely by analyzing several primary kinds of literature such as legislation, and legal theory to the views of scholars. The results obtained from this study are that Indonesia as a state of law certainly in its judicial system must obey the law. Indonesia is currently trying to impose electronic trials in resolving several cases in court through the use of electronic media such as teleconferences. This activity is based on the legislation governing electronic criminal trials such as PERMA Number 1 of 2019, PERMA Number 4 of 2020, the Criminal Code, and other related regulations. This regulation forms the basis for the implementation of electronic trials in Indonesia with the main objective of creating fast, simple, and inexpensive trials. However, the facts on the ground show that the problems that occur related to the implementation of this activity are not only technical problems or facilities and infrastructure but also public doubts about the quality of the results of the trial. This phenomenon also occurs in several countries that enforce electronic courts, such as the United States and the Netherlands. Therefore, there is a need for reformulation of statements in legislation so that it does not only focus on the goal of creating a fast, simple and inexpensive judiciary but also needs to be emphasized to ensure the proper legal process occurs.